(3JaSjQ ZQjH GdbQGfs - (3RjO Hf Ydj Hf GdMSjf Hf Ydj Hf CHj WGdH , CHh GdMSjf GdYdhqj GdgGTej GdbQTj , hjbGd dg (B((3RjO GdTgjO(B)(3,J (B122 (3g` s
(3ChdgG (B:s
(3bGd MOKfG GHh NGdO YeQh Hf NGdO GdhGSWi Yf GdGeGe Ydjge GdSdGe Gfg SFd Yf aGJMI GdcJGH abGd HSe Gddg gh JYXje ddg s
(3BNQgG (B:s
(3eG ef ehdhO EdG Ydi bdHg GdhShGS GdNfGS aEPG CZad aPcQ Gddg JYGdi NQL Pdc ef bdHI Je gPG GdaSjQ s
(3Vef eLehY s
(3QhGjI CHj NGdO YeQh Hf NGdO GdhGSWi hgh LRFjf ai eLdOs
(3bQf GdfSN (B:s
(3GdbQf GdKGdK YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B3 - (3U (B59 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B4 - (3U (B190s
(3JHUQGJ GdCUd (B:s
Keywords: (3eJaQbGJs